Pengaruh Tambahan Penghasilan Pegawai (Tpp) Terhadap Kinerja Pegawai Di Dinas Pendidikan Dan Kebudayaan Kabupaten Jeneponto - Mustakim, Maulya Naifah; Setiawati, Budi; Parawu, Hafiz Elfiansyah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study aimed to determine: how good  the effect of additional employee income (TPP), how the employee's performance , and how the influence  TPP  on employee performance partially and simultaneously at the Jeneponto Regency Education and Culture Office. This study was conducted for 2 months,  May to July 2020. The sampling technique was carried out using saturated sampling. The results of the validity instrument test showed rcount rtable which meant valid and reliability was above 0.7 It was reliable. The results of this study indicated a simple linear regression analysis that was above 0.5   it meant reliable, namely Y = a + bX = Y = 15,263 + 0.603 X t test results showed that the TPP variable had a positive effect on employee performance. The results of the F test showed that the independent variables had a positive effect on employee performance where the value of Pvalue was 0.000 0.05. The coefficient of determination (R2) showed the amount of contribution 0.371 or 37.1% of the TPP, while the remaining 62.9% was the contribution of other factors that were not examined in this study.Keywords: Performance, Employee, Income.